Infrastructural Readiness of Public Sector Talent Management in the Provincial Governments of South and Central Sulawesi - Maulida, St. Nurhikma; Musdalifah, Musdalifah (KnE Social Sciences, 2022)
This study of the readiness of public sector talent management infrastructure aimed to assess local government readiness for public sector talent management implementation, with a focus on provincial governments in South and Central Sulawesi. A qualitative approach was employed using a case study. Data were collected from the regional civil service agencies of the provincial governments of South and Central Sulawesi, using interviews and document analysis. According to the findings, provincial governments had prepared infrastructural support as part of public sector talent management implementation, including job mapping, talent profiles, assessment centers, competence tests, job competence standards, performance evaluation standards, career pattern human resource databases, talent management information systems, and funding. The previous implementation of a merit system policy boosted capital in assisting talent management implementation. Several issues hampered the implementation of talent management, including a lack of socialization about technical guidance for talent management, limited funding, policy overlap regarding civil service management, and a mismatch in the number of assessment centers and competence test assessors not being proportional to the number of employees in provincial governments. Keywords: talent, talent management, merit system